In constant search of the good: a qualitative study into insiders’ perspectives on living well with dementia - Yaron, Gili; Bakker, Franka; de Bruin, Simone (Frontiers in Psychiatry, 2024)
The new concept of 'living well with dementia' is currently gaining traction in practice, policy, and research. However, people with dementia and their carers' own understanding of this concept has not received much scholarly attention. This is because empirical studies into living well with dementia are predominantly quantitative; there are only a few qualitative studies on this topic. This study therefore sets out to investigate what living well means for 'insiders' in an everyday context.Methods: To explore insiders' own perspectives on living well with dementia, we conducted interviews and focus group discussions with 21 dementia stakeholders. The study included ten individuals with mild-to-moderate dementia living at home, five family carers who are or have been involved in the care for a person with dementia, and six health and social care professionals.Results: Living well with dementia, for our study participants, revolves around shaping their daily lives according to their values. In this sense, living well with dementia is no different than without. As it involves the values of the person with dementia and those of their social network, living well is both an individual and a collective concern. Having dementia undermines people living with the condition's ability to substantiate their values, but it is still possible to live well. As they attempt to shape living well with dementia, respondents encounter tensions within the social network and within the person with dementia. To handle these tensions, they work for mutual attunement by using sensitivity and switching between leading and following in social interactions.Discussion: Living well with dementia in a daily context is a dynamic process in which people with dementia, family carers, and professionals constantly seek the good together. This insight contributes to a better understanding of stakeholders' ongoing, invisible efforts to mutually attune. It may also help bypass dichotomizing approaches to dementia. Finally, it opens up new venues for research into reciprocity in the care collective. The article closes with recommendations to improve dementia care and support in light of these findings.